Dworkin on Dementia: Elegant Theory, Questionable Policy - Dresser, Rebecca (The Hastings Center report, 1995)
When patients have progressive and incurable dementia, should their advance directives always be followed? Contra Dworkin, Dresser argues that when patients remain able to enjoy and participate in their lives, directives to hasten death should sometimes be disregarded.